Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1128/cmr.00059-05
|View full text |Cite
|
Sign up to set email alerts
|

Human Pharmacogenomic Variations and Their Implications for Antifungal Efficacy

Abstract: SUMMARY Pharmacogenomics is defined as the study of the impacts of heritable traits on pharmacology and toxicology. Candidate genes with potential pharmacogenomic importance include drug transporters involved in absorption and excretion, phase I enzymes (e.g., cytochrome P450-dependent mixed-function oxidases) and phase II enzymes (e.g., glucuronosyltransferases) contributing to metabolism, and those molecules (e.g., albumin, A1-acid glycoprotein, and lipoproteins) involved in the distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 274 publications
(338 reference statements)
0
26
0
1
Order By: Relevance
“…Posaconazole is both a substrate and inhibitor of Pglycoprotein, but despite genetic polymorphisms resulting in significant variability in P-glycoprotein expression among racial groups, neither race nor ethnicity significantly affect the pharmacokinetics of posaconazole [23]. Single-nucleotide polymorphisms in UGT that encode uridine diphosphate-glucuronotransferase may play a role [24], but this has not been confirmed. Thus, the reasons for the intersubject bioavailability of posaconazole-a problem also observed with both itraconazole and voriconazole-remain poorly defined.…”
Section: Pharmacologymentioning
confidence: 97%
“…Posaconazole is both a substrate and inhibitor of Pglycoprotein, but despite genetic polymorphisms resulting in significant variability in P-glycoprotein expression among racial groups, neither race nor ethnicity significantly affect the pharmacokinetics of posaconazole [23]. Single-nucleotide polymorphisms in UGT that encode uridine diphosphate-glucuronotransferase may play a role [24], but this has not been confirmed. Thus, the reasons for the intersubject bioavailability of posaconazole-a problem also observed with both itraconazole and voriconazole-remain poorly defined.…”
Section: Pharmacologymentioning
confidence: 97%
“…For this reason, serum levels of hepatic enzymes are currently used as standard biomarkers for therapeutic monitoring, mainly of fungal infections. Pharmaco genomic models based on genetic polymorphisms of drug-metabolizing enzymes and drug transporters have the potential to improve medical decisions based on individual genomic profiles [54]. (Figure 2) presents an outlook of possible benefits of the cyclic interaction of TR, RTR and PM in the context of AK.…”
Section: Towards Precision Medicinementioning
confidence: 99%
“…Ocular toxicity of current anti-Acanthamoeba drugs [4,47,48,49] Proof of efficacy of off-label drugs [50,51] or novel anti-Acanthamoeba compounds previously approved in pre-clinical trials. Identification of the patient's drug metabolizing profile through pharmacogenomics tests [54] to implement personalized therapy Inflammatory response is mediated by TLR4 receptor [30] TLR4 as a therapeutic target. Identification of TLR4 polymorphisms [31] associated with differential prognosis and establishment of personalized therapy Available omics technologies, complex analysis tools and personal genome [39][40][41][42] Development of new biomarkers and genetic tests for prognosis, therapy selection and follow-up [43] …”
Section: Ak Patientmentioning
confidence: 99%
“…Therefore, it can be observed that genetic polymorphism plays an important role in the ADME parameters of drugs, and that the field of pharmacogenetics is blooming due to the necessity to better predict PK disposition of drugs in order to design individualized drug regimens that can better predict therapeutic effects and compliance. There are extensive reviews on this topic dealing with genetic polymorphisms of different molecules and their effect on PK and PD (Bolt et al, 2003;Kirchheiner et al, 2005;Sakaeda, 2005;Chen, 2006;Meletiadis et al, 2006).…”
Section: Genetic Polymorphismmentioning
confidence: 99%